Impact of smoothing conditions on the rounding effect of cutting edges of cemented carbide machining blades - Baczyński, Szymon; Cichosz, Piotr; Kuzinovski, Mikolaj; Tomov, Mite; Urych, Adam (SIMP Redakcja Mechanik - Agenda Wydawnicza SIMP, 2018)
The origin of rounding cutting edges of machining blades made out of cemented carbides is presented. Various methods of cutting edge smoothing and rounding measurement are described. The impact of smoothing conditions on the intensity and effects of edge rounding is specified.